Hybrid approach to assessing social cohesion as a factor in outperforming economic development - Slukin, H. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2025)
The article examines approaches to measuring social cohesion as a strategic economic resource for countries transitioning to advanced economic development. It is argued that social cohesion is a fundamental factor in advanced development through enhancing the effectiveness of human capital, ensuring resilience to crises, and creating institutional legitimacy. A systematic comparative analysis of four approaches to assessing cohesion is conducted: factorial, consequential, social network and institutional. The comparison is based on the parameters of the object of measurement, key indicators, conceptual limitations, data sources, resource intensity and international comparability. It was found that the factor approach provides identification of structural components of cohesion and high potential for international comparisons, but is characterised by high resource intensity. The outcome approach is most suitable for public administration due to annual data updates, but structural indicators do not always adequately reflect the actual level of cohesion. The social network approach captures economic effects through knowledge diffusion mechanisms, but demonstrates the lowest potential for international comparisons. The institutional approach is instrumental for assessing institutional prerequisites, but is characterised by dependence on the political situation. The necessity of developing a hybrid approach that integrates the advantages of individual methodologies is justified. The proposed approach is based on factor analysis to determine the significance of cohesion measurements, the formation of a system of indicators for policy monitoring, the development of clustering and autoregression models to assess the impact on economic development, the use of social network analysis for local studies, and institutional analysis to assess changes in the environment. A promising direction is the testing of a hybrid model for assessing social cohesion as a factor in economic development.